STATEMENT OF STANDARDS AND RESPONSIBILITIES UNDER PUBLIC ACCOUNTING INTERNSHIP PROGRAMS. (The Accounting Review, 1955)
The article presents those principles which seem to be basic to the operation of an accounting internship program in a manner which enables it to contribute most to the total accounting education of participating students. The article lists the goals of the internship programs, the responsibilities of each of the participants, and the standards which should be observed to make internship programs more effective educational devices. At present, in the U.S., over forty schools are operating internship plans of one type or another. Fundamentally they are all attempting to meet the same need, but the details of the plans vary considerably. There are variations of the basic plans, which aid in increasing the usefulness and effectiveness of internship programs. There is considerable variation also as to granting credit. A number of schools grant credit for internship work and grade students on performance. Internship programs have as their general objective the development of better qualified accountants with a resulting benefit to accounting firms, to students, and to schools.